Faktor-Faktor yang Mempengaruhi Kepatuhan Pajak UMKM dengan Preferensi Risiko sebagai Pemoderasi - Devita, Tia; Febriani, Eka (JEMAP, 2024)
Analyzing the factors that influence MSME tax compliance, that has been registered at The Samarinda Ilir’s Tax Office with Risk Preference as moderator is the aim of this research. The analysis used is SmartPLS 4.0 with 130 sample of respondents. This research found that the taxation understanding, tax services quality, and tax sanctions have significant and positive effect on tax payer’s compliance. Risk preference is moderating the effect tax services quality on tax compliance, but risk preference does not moderating the effect of the taxation understanding and taxation sanctions on tax compliance.